2017
DOI: 10.4018/ijgbl.2017100105
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Cognitive Bias with a Serious Game

Abstract: One of the benefits of using digital games for education is that games can provide feedback for learners to assess their situation and correct their mistakes. We conducted two studies to examine the effectiveness of different feedback design (timing, duration, repeats, and feedback source) in a serious game designed to teach learners about cognitive biases. We also compared the digital game-based learning condition to a professional training video. Overall, the digital game was significantly more effective tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Effects were observed up to 12 weeks after the training interventions, with relatively large effect sizes (e.g., Clegg et al, 2015;Morewedge et al, 2015;Rhodes et al, 2017). The largest effect sizes were observed in studies that involved repeated game playing (Dunbar et al, 2014(Dunbar et al, , 2017Clegg et al, 2015). This agrees with the finding that repetitive training increases retention (Cepeda et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Effects were observed up to 12 weeks after the training interventions, with relatively large effect sizes (e.g., Clegg et al, 2015;Morewedge et al, 2015;Rhodes et al, 2017). The largest effect sizes were observed in studies that involved repeated game playing (Dunbar et al, 2014(Dunbar et al, , 2017Clegg et al, 2015). This agrees with the finding that repetitive training increases retention (Cepeda et al, 2008).…”
Section: Discussionsupporting
confidence: 79%
“…Secondly, most studies involved only one training session, while repetition of training has been shown to increase retention effects in many different tasks and learning situations (e.g., Ausubel and Youssef, 1965;Cepeda et al, 2008). The present review found three out of the four studies with multiple training sessions indicating that playing the game twice resulted in more bias reduction than playing the game only once (Dunbar et al, 2014(Dunbar et al, , 2017Clegg et al, 2015). Lastly, there could be an effect of testing.…”
Section: S Single Playmentioning
confidence: 70%
See 2 more Smart Citations